Tertiary Level Exchange Students’ Perspectives on Self-Efficacy: Toward EFL Writing: Perspektif Siswa Pertukaran Tingkat Tersier tentang Kemanjuran Diri: Menuju Penulisan EFL - Megawati, Fika (JEES (Journal of English Educators Society), 2016)
This study aims to describe the students’ self-efficacy on their writing competence. Descriptive study was implemented by distributing closed-ended questionnaires in addition to interview and the result of writing task. The subjects of this study were three students from Thailand. The students’ responses in questionnaire were analyzed through frequency distribution and percentage. For the result of interview, it was transcribed in written form and used coding technique to classify the relevant points. The result of writing task became the supplementary data to confirm the findings and support conclusion. In a nutshell, the subjects of this study have moderate level of writing self-efficacy. Each student showed diverse selection in writing stage. The first student had moderate self-efficacy, but he relatively could cope with the writing problems. In the second student, the writing self-efficacy was the highest one, and it was proven from her better writing result. For the last student, similar to the writing quality, he considered himself weak in this skill.